Method for preparing high-compaction lithium manganese iron phosphate material by coating large particles with small particles

The method of covering large particles with small particles is prepared to prepare high -voltage and solid manganese iron lithium materials, solving the problem of low compact density and low capacity of traditional materials, and realizing the improvement of energy density and improving electrical performance.

CN119330325AActive Publication Date: 2025-01-21SICHUAN TIANLI LITHIUM ENERGY CO LTD

Patent Information

Application Number
CN202411541486.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Traditional lithium iron manganese phosphate materials have problems with low compaction density and gram capacity, which cannot meet the demand of power battery manufacturers for increased energy density.

Method used

Highly compacted lithium iron manganese phosphate materials are prepared by using a method of coating large particles with small particles. The raw material powder composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 is mixed with the carbon source glucose and water, and spray drying, sintering, and crushing are performed. The fired precursor materials with D50 of 5-10μm and 1-4μm are produced, and the final product is obtained through physical mixing and secondary sintering.

Benefits of technology

The compacted density and gram capacity of lithium iron manganese phosphate material are increased, which meets the needs of power battery manufacturers for energy density improvement, while reducing the resistivity and improving electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330325A_ABST
    Figure CN119330325A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a high-compaction lithium manganese iron phosphate material by coating large particles with small particles. The method comprises the following steps: mixing raw material powder consisting of Li2CO3, Mn3O4, FePO4 and LiH2PO4 with a carbon source glucose and water in a stirring tank; grinding the uniformly mixed material, then carrying out spray drying, carrying out primary sintering on the dried powder, and then crushing to prepare a primary sintering precursor material A; grinding the same mixed material, performing spray drying, performing primary sintering on the dried powder, changing the sintering temperature, and then crushing to prepare a primary sintering precursor material B; and mixing the primary sintering precursor material A and the primary sintering precursor material B, and performing secondary sintering to obtain a final product. According to the high-compaction lithium manganese iron phosphate material prepared by coating the large particles with the small particles, the compaction effect is improved, and meanwhile, the electrical property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium manganese iron phosphate material manufacturing, and in particular to a method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles. Background Art

[0002] As the upgrade direction of lithium iron phosphate batteries, lithium manganese iron phosphate has high safety and stability. Lithium manganese iron phosphate has an olivine structure, and Li+ ions can be embedded and removed from the crystal to realize the charging and discharging of lithium-ion batteries. During the process of lithium ion embedding and extraction, the crystal form can be maintained stable, with good stability, ensuring the safety and high cyclicity of the battery. Compared with lithium iron phosphate, although the theoretical gram capacity of both is about 170mAh / g, the overall discharge platform of lithium manganese iron phosphate is 3.8V~4.1V, while the theoretical discharge platform of lithium iron phosphate is 3.4V, the actual level is 3.2~3.3V, and the energy density can be about 15%~25% higher.

[0003] However, in practical applications, traditional lithium iron manganese phosphate has problems with low compaction density and gram capacity (generally compaction density is between 2.1 and 2.2 g / cm³, and gram capacity is between 135 and 150 mAh / g), which cannot meet the urgent needs of power battery manufacturers for improving energy density. Therefore, it is necessary to develop higher performance lithium iron manganese phosphate positive electrode materials.

[0004] To this end, the present invention is specially proposed to solve the above-mentioned technical problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a high-density lithium manganese iron phosphate material by coating a large particle with a small particle, comprising the following steps: (1) mixing raw material powders consisting of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank; (2) grinding the uniformly mixed materials in step (1) in a sand mill and then spray drying, sintering the dried powder once, and then crushing to prepare a sintered precursor material A with a D50 of 5 to 10 μm; (3) The same mixed material is obtained in the manner of step (1), ground in a sand mill and then spray dried, the dried powder is sintered once, the sintering temperature is changed, and then crushed to prepare a sintered precursor material B with a D50 of 1 to 4 μm; (4) The first-fired precursor material A and the second-fired precursor material B are mixed by physical mixing and then subjected to secondary sintering to obtain the final product.

[0006] Preferably, the raw materials, carbon source glucose and water in step (1) are mixed in a ratio of 28:7:65 by weight.

[0007] Preferably, the raw material powder composed of Li2CO3, Mn3O4, FePO4 and LiH2PO4 is mixed according to the molar ratio of Li:Mn:Fe:P=(1.01~1.05):0.6:0.4:(0.96~1).

[0008] Preferably, the raw material powder composed of Li2CO3, Mn3O4, FePO4 and LiH2PO4 is mixed according to the molar ratio of Li:Mn:Fe:P=1.02:0.60:0.4:0.98.

[0009] Preferably, the sintering temperature in step (2) is a constant temperature of 700° C., and the sintering constant temperature time is 9 hours.

[0010] Preferably, the sintering temperature in step (3) is a constant temperature of 650° C., and the sintering constant temperature time is 9 hours.

[0011] Preferably, the grinding conditions in steps (2) and (3) are grinding to 0.3 μm at D50.

[0012] Preferably, the physical mixing in step (4) is carried out in a ratio of 90% large particles and 10% small particles.

[0013] Preferably, the temperature of the secondary sintering in step (4) is a constant temperature of 600°C.

[0014] Preferably, the carbon content after the first sintering in steps (2) and (3) accounts for 1.45% to 1.55% by weight.

[0015] Preferably, the powder dried in steps (2) and (3) is sintered once under closed N2 conditions.

[0016] Preferably, the finished product after secondary sintering in step (4) is compacted to obtain a final product at 2.3 to 2.5 g / cm³.

[0017] The beneficial effects of the present invention are: Compared with the traditional lithium iron manganese phosphate, the compaction density of the present invention is improved, and the gram capacity is significantly improved, which can meet the urgent needs of power battery manufacturers for improving energy density; The small particles of the present invention cover the large particles to prepare the high-density lithium manganese iron phosphate material, which improves the compaction effect. At the same time, when the compaction density is increased, the gaps between the particles are reduced, the electron conduction barrier is reduced, and the resistivity is reduced, which plays a role in improving the electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a scanning electron microscope (SEM) image of a calcined precursor material A; Figure 2 A scanning electron microscope (SEM) image of a high-density lithium manganese iron phosphate material prepared by coating large particles with small particles of the present invention. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0020] Example 1 A method for preparing a high-density lithium manganese iron phosphate material by coating large particles with small particles in this embodiment includes the following steps: (1) Mixing raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank, with the mixing ratio being 28:7:65 in parts by weight, wherein the raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 are proportioned according to the molar ratio of Li:Mn:Fe:P=1.05:0.6:0.4:1; (2) The materials mixed in step (1) are ground in a sand mill to a D50 of 0.3 μm and then spray dried. The dried powder is sintered once at a constant temperature of 700° C. in a closed N2 condition for 9 hours, and then crushed to prepare a sintered precursor material A with a D50 of 5 to 10 μm; (3) The same mixed material is obtained in the manner of step (1), and the D50 is ground to 0.3 μm in a sand mill and then spray dried. The dried powder is sintered once under closed N2 conditions, the sintering temperature is changed to a constant temperature of 650°C, the sintering constant temperature time is 9 h, and then crushed to prepare a sintered precursor material B with a D50 of 1 to 4 μm; (4) The first-fired precursor material A and the first-fired precursor material B are mixed in a physical manner in a ratio of 60% to 90% of large particles and 10% to 40% of small particles, and then secondary sintering is performed. The temperature of the secondary sintering is constant at 600°C. The finished product after the secondary sintering is compacted to obtain a final product at 2.3 to 2.5 g / cm³.

[0021] Example 2 A method for preparing a high-density lithium manganese iron phosphate material by coating large particles with small particles in this embodiment includes the following steps: (1) Mixing raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank, with the mixing ratio being 28:7:65 in parts by weight, wherein the raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 are proportioned according to the molar ratio of Li:Mn:Fe:P=1.03:0.6:0.4:0.985; (2) The materials mixed in step (1) are ground in a sand mill to a D50 of 0.3 μm and then spray dried. The dried powder is sintered once at a constant temperature of 700° C. in a closed N2 condition for 9 hours, and then crushed to prepare a sintered precursor material A with a D50 of 5 to 10 μm; (3) The same mixed material is obtained in the manner of step (1), and the D50 is ground to 0.3 μm in a sand mill and then spray dried. The dried powder is sintered once under closed N2 conditions, the sintering temperature is changed to a constant temperature of 650°C, the sintering constant temperature time is 9 h, and then crushed to prepare a sintered precursor material B with a D50 of 1 to 4 μm; (4) The first-fired precursor material A and the first-fired precursor material B are mixed in a physical manner in a ratio of 60% to 90% of large particles and 10% to 40% of small particles, and then secondary sintering is performed. The temperature of the secondary sintering is constant at 600°C. The finished product after the secondary sintering is compacted to obtain a final product at 2.3 to 2.5 g / cm³.

[0022] Example 3 A method for preparing a high-density lithium manganese iron phosphate material by coating large particles with small particles in this embodiment includes the following steps: (1) Mixing raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank, with the mixing ratio being 28:7:65 in parts by weight, wherein the raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 are proportioned according to the molar ratio of Li:Mn:Fe:P=1.01:0.6:0.4:0.96; (2) The materials mixed in step (1) are ground in a sand mill to a D50 of 0.3 μm and then spray dried. The dried powder is sintered once at a constant temperature of 700° C. in a closed N2 condition for 9 hours, and then crushed to prepare a sintered precursor material A with a D50 of 5 to 10 μm; (3) The same mixed material is obtained in the manner of step (1), and the D50 is ground to 0.3 μm in a sand mill and then spray dried. The dried powder is sintered once under closed N2 conditions, the sintering temperature is changed to a constant temperature of 650°C, the sintering constant temperature time is 9 h, and then crushed to prepare a sintered precursor material B with a D50 of 1 to 4 μm; (4) The first-fired precursor material A and the first-fired precursor material B are mixed in a physical manner in a ratio of 60% to 90% of large particles and 10% to 40% of small particles, and then secondary sintering is performed. The temperature of the secondary sintering is constant at 600°C. The finished product after the secondary sintering is compacted to obtain a final product at 2.3 to 2.5 g / cm³.

[0023] Example 4 A method for preparing a high-density lithium manganese iron phosphate material by coating large particles with small particles in this embodiment includes the following steps: (1) Mixing raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank, with the mixing ratio being 28:7:65 in parts by weight, wherein the raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 are proportioned according to the molar ratio of Li:Mn:Fe:P=1.02:0.6:0.4:0.98; (2) The materials mixed in step (1) are ground in a sand mill to a D50 of 0.3 μm and then spray dried. The dried powder is sintered once at a constant temperature of 700° C. in a closed N2 condition for 9 hours, and then crushed to prepare a sintered precursor material A with a D50 of 5 to 10 μm; (3) The same mixed material is obtained in the manner of step (1), and the D50 is ground to 0.3 μm in a sand mill and then spray dried. The dried powder is sintered once under closed N2 conditions, the sintering temperature is changed to a constant temperature of 650°C, the sintering constant temperature time is 9 h, and then crushed to prepare a sintered precursor material B with a D50 of 1 to 4 μm; (4) The first-fired precursor material A and the first-fired precursor material B are mixed in a physical manner in a ratio of 60% to 90% of large particles and 10% to 40% of small particles, and then secondary sintering is performed. The temperature of the secondary sintering is constant at 600°C. The finished product after the secondary sintering is compacted to obtain a final product at 2.3 to 2.5 g / cm³.

[0024] Comparative Example 1 A method for preparing a high-density lithium manganese iron phosphate material by coating large particles with small particles in this embodiment includes the following steps: (1) Mixing raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank, with the mixing ratio being 28:7:65 in parts by weight, wherein the raw material powders composed of Li2CO3, Mn3O4, FePO4, and LiH2PO4 are proportioned according to the molar ratio of Li:Mn:Fe:P=1.05:0.6:0.4:1; (2) The material mixed in step (1) is ground in a sand mill to a D50 of 0.3 μm and then spray dried. The dried powder is sintered once at a constant temperature of 700°C in a closed N2 atmosphere for 9 hours, and then crushed to prepare a final product with a D50 of 5 to 20 μm.

[0025] Comparative Example 2 A method for preparing a high-density lithium manganese iron phosphate material by coating large particles with small particles in this embodiment includes the following steps: (1) Mix raw material powders consisting of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank in a mixing ratio of 28:7:65 by weight, wherein Li2CO3, Mn3O4, The raw material powder composed of FePO4 and LiH2PO4 is proportioned according to the molar ratio of Li:Mn:Fe:P=1.01:0.6:0.4:0.96; (2) The material mixed in step (1) is ground in a sand mill to a D50 of 0.3 μm and then spray dried. The dried powder is sintered once at a constant temperature of 700°C in a closed N2 atmosphere for 9 hours, and then crushed to prepare a final product with a D50 of 5 to 20 μm.

[0026] Actual test Compacted density test: 1.00 g of the lithium manganese iron phosphate positive electrode material prepared in the above examples and comparative examples was weighed and added into the material chamber of a compacted density test instrument, and the compacted density was tested under a certain pressure according to the process requirements.

[0027] Capacity test: The lithium iron manganese phosphate positive electrode material prepared in the above embodiment and comparative example was used to prepare a button cell for electrochemical performance test. The specific steps include: mixing the lithium iron manganese phosphate positive electrode material, the conductive agent cnt and the binder PVDF in NMP at a ratio of 90:5:5, coating the mixture on aluminum foil and drying it in a vacuum drying oven. After drying, assembling the battery in an argon glove box, pressing the positive electrode sheet with a tablet press, the negative electrode is a metal lithium sheet, the electrolyte is 1 mol / L LiPF6-EC:DMC (volume ratio 1:1), and a polypropylene porous membrane is used as a diaphragm. The parameter conditions selected for testing the electrochemical performance are: the test voltage range is 2.5-4.3V, and the compaction effect, discharge condition and resistivity of the test are shown in Table 1.

[0028] Table 1 It can be seen from the table that compared with Comparative Examples 1 and 2, the compaction density of the embodiments is increased by more than 0.3, and the resistivity is improved. This is because the small particles coated on the surface of the large particles can fill the gaps in the large particles, thereby improving the compaction effect. When the compaction density increases, the gaps between the particles decrease, the electron conduction barrier is reduced, and the resistivity is reduced, which improves the electrical performance.

[0029] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles, characterized in that: The following steps are involved: (1) mixing raw material powders consisting of Li2CO3, Mn3O4, FePO4, and LiH2PO4 with carbon source glucose and water in a stirring tank; (2) grinding the uniformly mixed materials in step (1) in a sand mill and then spray drying, sintering the dried powder once, and then crushing to prepare a sintered precursor material A with a D50 of 5 to 10 μm; (3) The same mixed material is obtained in the manner of step (1), ground in a sand mill and then spray dried, the dried powder is sintered once, the sintering temperature is changed, and then crushed to prepare a sintered precursor material B with a D50 of 1 to 4 μm; (4) The first-fired precursor material A and the second-fired precursor material B are mixed by physical mixing and then subjected to secondary sintering to obtain the final product.

2. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The raw materials, carbon source glucose and water in step (1) are mixed in a ratio of 28:7:65 by weight.

3. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 2, characterized in that: The raw material powders composed of Li2CO3, Mn3O4, FePO4 and LiH2PO4 are mixed according to the molar ratio of Li:Mn:Fe:P=(1.01-1.05):0.6:0.4:(0.96-1).

4. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 3, characterized in that: The raw material powders composed of Li2CO3, Mn3O4, FePO4 and LiH2PO4 are mixed according to the molar ratio of Li:Mn:Fe:P=1.02:0.60:0.4:0.

98.

5. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The sintering temperature in step (2) is a constant temperature of 700° C., and the sintering constant temperature time is 9 hours.

6. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The sintering temperature in step (3) is a constant temperature of 650° C., and the sintering constant temperature time is 9 hours.

7. The method for preparing high-density lithium iron manganese phosphate material by coating large particles with small particles according to claim 1, characterized in that: The grinding conditions in steps (2) and (3) are grinding to 0.3 μm at D50.

8. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: In step (4), the physical mixing is performed in a ratio of 60% to 90% for large particles and 10% to 40% for small particles.

9. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The temperature of the secondary sintering in step (4) is a constant temperature of 600°C.

10. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The carbon content after the first sintering in steps (2) and (3) accounts for 1.45% to 1.55% by weight.

11. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The powder dried in steps (2) and (3) is sintered once under closed N2 conditions.

12. The method for preparing high-density lithium manganese iron phosphate material by coating large particles with small particles according to claim 1, characterized in that: The finished product after secondary sintering in step (4) is compacted to obtain the final product at 2.3-2.5 g / cm³.

Citation Information

Patent Citations

  • High-tap-density lithium iron manganese phosphate positive electrode material, preparation method and applications thereof

    CN109250698A

  • Preparation method of high-compaction lithium iron phosphate

    CN111392705A

  • Preparation method and application of lithium manganese iron phosphate

    CN115231541A

  • Preparation method of solid-phase high-compaction lithium manganese iron phosphate positive electrode material and product thereof

    CN115924874A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN116692812A

Cited By

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN121823504A